Microbiological contamination in different food service units associated with food handling - Alves, A (2021)
Background: A microbiological analysis of samples taken from hands of food handlers and utensils/crockery in food service units was used to assess the risk of food contamination. We aimed to assess indicators of microbiological contamination in different food service units. Methods: We used data for an official inspection proposal (2018–2019) in different food service units serving a district in Northeast Portugal. We showed the proportion of positive samples for each microorganism assessed in samples taken from hands and kitchen utensils/crockery. Results: Out of 471 samples taken from hands of food handlers, 26.8% (n = 126) were classified as “unsatisfactory” due to the presence of at least Escherichia coli, Staphylococcus aureus and/or total and fecal coliforms. Such a proportion varied according to the type of food service unit with a higher proportion being observed in Canteens (40.0%) and in Retirement Home/Day Care Centers (37.8%). More than one third of 649 samples taken from kitchen utensils/crockery were classified as “unsatisfactory” (n = 181; 27.9%) or “bad” (n = 49; 7.6%). There were significant differences in these proportions across food service units, with a higher proportion of “unsatisfactory” samples being observed in Fishmongers and Butcher Shops/Charcuteries (50.0% and 45.1%, respectively), while a higher proportion of “bad” samples was observed in both Pastry/Bakery and Fishmonger establishments (33.3%), followed by Butcher Shops/Charcuteries (14.1%). Conclusions: Our results emphasize the need of awareness of hygiene practices among food handlers of different food service units, particularly in Fishmongers, Pastry/Bakery establishments and Butcher Shops/Charcuteries, highlighting the need of a periodic hygienic evaluation.